2019
DOI: 10.1186/s12966-019-0855-9
|View full text |Cite|
|
Sign up to set email alerts
|

Individualized home-based exercise and nutrition interventions improve frailty in older adults: a randomized controlled trial

Abstract: Background: Frail older adults are predisposed to multiple comorbidities and adverse events. Recent interventional studies have shown that frailty can be improved and managed. In this study, effective individualized home-based exercise and nutrition interventions were developed for reducing frailty in older adults. Methods: This study was a four-arm, single-blind, randomized controlled trial conducted between October 2015 and June 2017 at Miaoli General Hospital in Taiwan. Overall, 319 pre-frail or frail older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(210 citation statements)
references
References 46 publications
5
183
2
1
Order By: Relevance
“…Thus, frailty among the individuals with chronic disease requires more attention. Moreover, studies suggest frailty is reversible and can be treated and delayed by interventions, such as health promotion, nutrition, physical, and social support [ 10 , 11 , 12 , 13 ]. Therefore, with the rapid growth of aging population, special attentions should be paid on exploring risk factors and preventing frailty among the older adults with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, frailty among the individuals with chronic disease requires more attention. Moreover, studies suggest frailty is reversible and can be treated and delayed by interventions, such as health promotion, nutrition, physical, and social support [ 10 , 11 , 12 , 13 ]. Therefore, with the rapid growth of aging population, special attentions should be paid on exploring risk factors and preventing frailty among the older adults with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the previously mentioned lack of a standard definition for frailty, only studies utilizing a valid construct to define frailty for inclusion criteria were included. In total, 8 studies were included in this narrative review [15][16][17][18][19][20][21][22] (results from one intervention was published in four separate articles) [15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed 8 studies (Table 1) [15][16][17][18][19][20][21][22]. The analyzed interventions included a total sample of 1030 communityliving older adults (53% women) with a mean age of 79.6 ± 7.1 years.…”
Section: Participants and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [1], the author reported that an abbreviation was incorrect in the original article; In the Appendix the abbreviation ‘cal’ was incorrect. The correct abbreviation is ‘kcal’.…”
mentioning
confidence: 99%